The Influence of the Implementation of Internal Control Concepts on Fraud Prevention at PT. Bank Sulselbar with Religiosity as a Moderating Variable - Hamdan, Hamdan; Amiruddin, Amiruddin; Achmad , Hamzah (Economos : Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study is to analyze the effect of the application of the concept of internal control on fraud prevention at PT. Bank Sulselbar both directly and when moderated by the variable of religiosity. This research uses a quantitative approach that uses data in the form of numbers and statistics to test hypotheses, identify patterns, and draw conclusions. Quantitative research focuses on collecting, analyzing, and interpreting quantitative data in order to understand the phenomenon under study. The results showed that internal control has a positive and significant influence on fraud prevention at PT. Bank Sulselbar. With the implementation of good internal control, PT. Bank Sulselbar can identify, prevent, and reduce potential fraud that can harm bank operations and reputation. Furthermore, religiosity cannot moderate significantly between internal control over fraud prevention at PT. Bank Sulselbar. Although religious factors may provide ethical and moral guidance for individuals, the study suggests that in the context of internal control and fraud prevention in financial institutions, religiosity does not significantly moderate the relationship.